La mort en ligne, le cimetière virtuel et l’architecture des rites funéraires postmodernes - Ţenescu, Alina (Romanica Silesiana)
This paper makes use of different disciplinary methodologies in order to analyze the issue of death and representation of funerary rites within the universe of the cyberspace, in order to propose a balanced integrative vision of the function and role of recurrent non‑places within the virtual space: the electronic cemeteries with their specific rituals. Starting from an anthropo‑semio‑semantic approach and using the comparatist method, the article analyzes the specificity of funerary rites (counter‑rituals) and ceremonies related to online memorials and electronic cemeteries pertaining to different cultural spaces (French, Romanian, Indian, English‑American and so on). Key words: death, funerary rites, rituals, electronic cemeteries, online memorials, non‑places, postmodernism